Experimental and numerical investigation on effects of thickness of NCM622 cathode in Li-ion batteries for high energy and power density. (15th January 2023) - Kang, Jihyeon; Atwair, Mohamed; Nam, Inho; Lee, Chul-Jin
Abstract: The electrode thickness is one of the most important design strategies for enhancing the energy density of lithium-ion batteries in practical applications. However, thick electrodes suffer from severe capacity loss because of the limited Li + ion diffusion. Herein, we reveal the optimum point for high energy and power density by investigating the rated capacity that is dependent on the electrode thickness and C-rates using a pseudo-two-dimensional model-based simulation and experimental results. The experimental results showed that the cathode (NCM 622) with a thickness of 86 μm had the most stable performance in the range of C-rates from 0.1C to 2C. In contrast, the optimal thickness in the simulation was 104 μm for a various range of C-rates, indicating the difference in the capacity loss between the experiment and simulation with increasing C-rate. The disparity in the rated capacity between the simulation and experiment is attributed to the inhomogeneity inside the cathode with the increase in mechanical cracks. Based on the experimental and simulation results, we present new insights on the importance of a completed uniform electrode film for high-power NCM 622 cathodes to develop a practical fabrication method for maximum capacity while maintaining high energy and power density. Highlights: Varying electrode thickness for optimization can enhance LIB energy and power density. Simulation results show good agreement with experimental results at low current density. Inhomogeneity inside thick electrodes caused a significant capacity loss in experiments. Optimum thickness was determined using experimental and simulation results.